'Has Aboriginal art a future?' Leonhard Adam's 1944 essay and the development of the Australian Aboriginal art market. (March 2015) - Sloggett, Robyn
This article examines how foresight, hindsight and perception are enabled, modified and compromised by competing intellectual traditions and by social and professional exigencies. Focusing on the example of one scholar, Dr Leonhard Adam, and his essay 'Has Aboriginal art a future?' this article charts the trajectory of this question from obscurity to celebration. It explores why such a significant question was unable to ignite debate, at a time when there was considerable interest in the role of Aboriginal art in the articulation of national identity. It examines the intellectual and social conditions that framed Adam's contribution and explores what enabled him, as a relative outsider, to develop such a prescient understanding of the future of Australian Aboriginal art.